2008
DOI: 10.1080/09513590801895575
|View full text |Cite
|
Sign up to set email alerts
|

Serum pro-inflammatory cytokines in physiological and pre-eclamptic pregnancies

Abstract: Results of this study do not support standard screening for pro-inflammatory cytokines (TNF-alpha, IL-1, IL-6 and IFN-gamma) in pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 15 publications
0
18
1
Order By: Relevance
“…In this study, we found that there was no significant change in the levels of IL1b in the serum of women with PE compared with normal pregnancy. There is a controversy about IL-1b in PE, while some authors reported increased blood serum levels compared with normal pregnant women [33], some were not able to detect a significant difference between the serum IL-1b levels of normal pregnant and preeclamptic women, similar to our study [34,35]. In summary, TNF-a and IL-1b were not found to be increased in preeclamptic pregnancies.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In this study, we found that there was no significant change in the levels of IL1b in the serum of women with PE compared with normal pregnancy. There is a controversy about IL-1b in PE, while some authors reported increased blood serum levels compared with normal pregnant women [33], some were not able to detect a significant difference between the serum IL-1b levels of normal pregnant and preeclamptic women, similar to our study [34,35]. In summary, TNF-a and IL-1b were not found to be increased in preeclamptic pregnancies.…”
Section: Discussioncontrasting
confidence: 59%
“…There is a conflict on TNF-a level in PE in the literature. Although several studies have reported elevated circulating TNF-a in patients with PE [30][31][32][33], others failed to detect a correlation between TNFa and the later onset of PE [34,35]. Therefore, we investigated both macrophage activity and TNF-a and IL-1b cytokines in PE in relation to macrophages activity.…”
Section: Discussionmentioning
confidence: 94%
“…Although small case-control studies have reported significant associations between various immune biomarkers and preeclampsia in the third trimester,[8, 1117] these results have not been replicated in other investigations [18–23]. The most consistent associations have been found with IL-6, TNFα and IL-8.…”
Section: Introductionmentioning
confidence: 83%
“…On the contrary, others did not manage to identify a correlation between maternal serum levels of IL-6 or TNF-alpha and preeclampsia [19, 20]. Furthermore, Montagnana et al [29] based on their results concluded that preeclampsia screening based on cytokines such as IL-6 or TNF-alpha is not proposed.…”
Section: Discussionmentioning
confidence: 99%